Analisis Tindak Tutur Dalam Wacana Parenting Podcast Mom’s Cornet Nikita Willy. - NURFADILLAH; Zulfiani ramaadhani azis; Abdul Halik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to analyze the forms and intent of expressive, assertive,directive, and commissive speech acts in mom's cornet Nikita Willy's podcast. This type ofresearch is descriptive research using a qualitative approach. The data from this studycame from the Mom's Cornet podcast hosted by Nikita Willy with the title "Benefits ofexploration for children" The data used in this study are a number of dialogues andinteractions that are identified as forms of expressive, assertive, directive, and commissivespeech acts. The data collection technique in this study uses two methods, namely listeningand note-taking techniques. The results of this study indicate that communication in thecontext of parenting involves various types of speech acts that reflect the emotions,information, and commitment of the speaker. In the Nikita Willy podcast, expressive,assertive, directive, and commissive speech acts were found.